Penerapan Supervisi Akademik Dalam Pemanfaatan Lingkungan Sekolah Sebagai Sumber Belajar Bagi Guru SD Negeri 19 Seluma Tahun Pelajaran 2017/2018 - Hamidan, Hamidan (Gayaku Publisher, 2022)
This research of background by lowering of enthusiasm learn in exploiting environment go to school as source learn. More teacher rely on source learn which as described in teacher book. To motivate the spirit of teacher dig various source learn hence researcher of have initiative to execute adjacently of construction pass applying of akademik supervise in exploiting environment go to school as source learn. From applying of cycle of I, teacher capable to exploit environment go to school as source learn high category newly 1 teacher (17%), category is teacher (50%) and low category is 2 teacher (its 33%) meaning of teacher performance capable to in cycle of I new 67 . This result not yet is up to standard of hoped goals so that repair of action require to cycle pad hereinafter. Hereinafter at cycle of II,showing ability 3 teacher (50%) at high category score, 2 teacher or 33% at category is and 1 teacher (17%) at low category. If percentage of teacher capable to process and exploit environment go to school as source learn to reach 83%. Result of action at cycle of II show scientifically that applying of akademik supervise can improve ability of teacher of SDN 19 Seluma in the year lesson 2017/2018 in exploiting environment go to school as source learn.